Response to ‘Learner perception regarding the lecture and the small group discussion as Teaching/ Learning methods in Physiology’ (Bangladesh Journal of Medical Science, 2019)
Abstract not availableBangladesh Journal of Medical Science Vol.19(1) 2020 p.174-175